PENGEMBANGAN NILAI-NILAI BUDAYA KERCENGAN UNTUK MENINGKATKAN EMOTIONAL RESILIENCE MAHASANTRI - Apriliyanti; Dr. Mudafiatun Isriyah,S.Pd., M.Pd2; Weni Kurnia Rahmawati,S.Pd., M.Pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop the values ​​of Kercengan culture as a means of character education to increase the emotional resilience of female students at the Ibnu Katsir Islamic Boarding School in Jember. Kercengan culture, as a local cultural heritage of Bawean, contains noble values ​​such as togetherness, solidarity, mutual respect, social support, and spirituality. This study uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects involved female students and their mentors at the Ibnu Katsir Islamic Boarding School in Jember. Data were collected through observation, interviews, and questionnaires which were analyzed qualitatively and quantitatively descriptively. The results of the study indicate that the integration of Kercengan Culture values ​​in learning activities and emotional development can increase students' awareness of personal, social, and spiritual emotional resilience. Students become better at carrying out daily tasks or activities at the boarding school, and show initiative in Islamic boarding school life. Expert validity tests and user responses indicate that the development product based on Kercengan cultural values ​​is feasible and effective to be applied as an emotional education medium. This study emphasizes the importance of revitalizing cultural values ​​as a contextual strategy in emotional education in Islamic boarding schools.